A study on miscibility properties of polyacrylonitrile blending films with biodegradable polymer, shellac. (April 2023) - Cho, Beom-Gon; Lee, Jung-Eun; Jeon, Seung-Yeol; Chae, Han Gi
Abstract: Polyacrylonitrile (PAN) films blended with shellac, biodegradable polymer, were prepared via simple solution casting method. The miscibility of PAN with shellac polymer was investigated and the optimal concentration of shellac in terms of hydrogen bonding between shellac and PAN chain was determined to be used as a novel biomass carbon precursor. Shellac and PAN chain could exert interaction and the interaction facilitates to loose the crystalline structure of the PAN chain, suggesting that the decrease of the oxidation temperature of the PAN chain in the PAN/shellac blends film by the introduction of shellac segments. The optimal PAN/shellac blends film exhibited outstanding mechanical performances (73.8% higher tensile strength, 60% higher storage modulus compared with control PAN film) showing homogeneous blending state. Highlights: The PAN film was prepared by simple solution casting through blending with shellac, which is the biomass-polymer material. The optimal concentration of shellac (5 wt%) was confirmed resulting in the highest miscibility between PAN and shellac. The improvement of mechanical performances of the films resulted from effective hydrogen bonding between shellac and PAN. This study is the first attempt to make PAN blends with shellac for possibility of the application of new biomass polymer.